The EuQoS system a solution for QoS routing in heterogeneous networks. - Masip-Bruin, Xavi.
EuQoS is the acronym for "end-to-end quality of service support over heterogeneous networks", which is a European research project aimed at building an entire QoS framework, addressing all the relevant network layers, protocols, and technologies. This framework, which includes the most common access networks (xDSL, UMTS, WiFi, and LAN) is being prototyped and tested in a multidomain scenario throughout Europe, composing what we call the EuQoS system. In this article we present the novel QoS routing mechanisms that are being developed and evaluated in the framework of this project. The preliminary performance results validate the design choices of the EuQoS system, and confirm the potential impact this project is likely to have in the near future.
Keywords: EuQoS system; LAN; QoS routing; UMTS; WiFi; Access networks; End-to-end quality of service support; Heterogeneous networks; xDSL